Characterisation of community-acquired Staphylococcus aureus causing skin and soft tissue infections in a children's hospital in Shanghai, China. (2019) - Wang, Xing; Shen, Yanyun; Huang, Weichun; Zhou, Yun
Abstract: Community-acquired Staphylococcus aureus is a major pathogen responsible for skin and soft tissue infections (SSTIs). This study aimed to investigate the prevalence and molecular characteristics of community-acquired S. aureus isolates recovered from paediatric patients with SSTIs in Shanghai, China. Between January 2015 and January 2018, 91 community-acquired S. aureus isolates were characterised by antibiotic susceptibility, multilocus sequence typing (ST), staphylococcal protein A gene ( spa ) type and virulence genes. Methicillin-resistant S. aureus (MRSA) strains were also characterised by staphylococcal cassette chromosome mec (SCC mec ) type. Forty-one (45.1%) S. aureus isolates were MRSA. ST59 (33.0%, 30/91) was the most common sequence type, and t437 (18.7%, 17/91) was the most common spa type. SCC mec IV and V accounted for 61.0% and 34.1% of all MRSA isolates, respectively. Each isolate carried at least six virulence genes. The positive rates of Panton-Valentine leukocidin genes among all S. aureus, MRSA and methicillin-susceptible S. aureus isolates were 30.8% (28/91), 39.0% (16/41) and 24% (12/50), respectively. The prevalence of community-associated MRSA was surprisingly high among children with community-acquired SSTIs in Shanghai. ST59-t437 was the most prevalent community-acquired S. aureus clone causing SSTIs.